Blast wave propagation characteristics in FPSO: Effect of cubical obstacles. (15th April 2022) - Fang, Han; Xue, Hongxiang; Tang, Wenyong
Abstract: Gas explosion accidents may result in catastrophic damage to structures and humans. Generally, the gas explosion pressures on Floating, Production, Storage, and Off-loading unit (FPSO) are affected by the obstacles. In this paper, the numerical simulation method is applied to study the blast wave propagation in the modules of FPSO. The types of the blast wave, dimensions of the obstacle, and combinations of multiple obstacles are regarded as the variables to study the change of explosion pressure fields. An effect coefficient η is defined to represent the effect of the obstacles on explosion pressures. Results show the obstacles can only affect the finite areas in the surrounding. The explosion pressures on the front or side of the obstacle only depend on the intensities of incident waves. However, the pressures at the back of the obstacle are determined by the path difference of the diffraction waves, which is sensitive to obstacle dimensions. Extending the width and height significantly reduces the explosion pressures behind the obstacle. Analyzing the effect coefficients in the multi-obstacle combinations, reveals the medium spacing distance can reduce the explosion pressure. Based on the analysis results, some suggestions are recommended for escape and refuge. Highlights: Cause for the different features of blast wave propagation on the two floors of FPSO are analyzed. Effect of the reflection wave and diffraction wave on the tendency and peak feature of pressure curves is summarized. Effect of obstacle dimensions on the pressure reduction result behind obstacle are analyzed. Analyzing the effect of obstacle spacing on the blast wave propagation in three multiple obstacle combinations. Giving the pressure enhancement and reduction region in the obstacle combinations to provide the recommendation of escape and refuge.